Protein-Ligand Interactions: Target Identification and Drug Discovery - Altieri, Fabio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Bioactive compounds and drugs are designed and screened on the basis of specific molecular targets as well as via the identification of active ingredients from traditional medicine or by serendipitous discovery. The development of novel therapeutic strategies not only requires a deep knowledge of the molecular processes and the cellular pathways involved in each pathological condition and disease, but also the specific protein targets and the effects of drug binding on protein conformation and activity. Understanding of how drugs can modify and modulate specific cellular pathways and functions will be helpful during the process of drug development and clinical trials.